THE EFFECT OF KARAMUNTING (Rhodomyrtus Tomentosa) LEAF EXTRACT ON THE NUMBER OF MACROPHAGES IN PULP INFLAMMATION - Indah Septiani; Muhammad Yanuar Ichrom Nahzi; Nolista Indah Rasyid (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: Reversible pulpitis is an inflammation of dental pulp caused by the opening of the pulp due to cavities. One of the procedures in exposed pulp treatment is direct pulp capping using calcium hydroxide. However, this material has side effects, its high pH can cause necrosis, and due to that, a safer alternative material is needed. Karamunting leaf extract contains phenolic compounds, flavonoids, tannins, and saponins which have immunomodulatory properties that play an important role in healing exposed pulp. Objective: To determine the effect of karamunting leaf extract on the number of macrophages in pulp inflammation. Methods: This was a true experimental research with posttest-only group design, using simple random sampling that consist of 24 male Wistar rats which later be divided into 3 groups. The perforated rat dental pulp was then treated with karamunting leaf extract as a treatment group, calcium hydroxide as a positive control group, and not given any application (without drug) as a negative control group. The samples were analyzed histologically on the 3rd to 7th day after the application, inflammatory response occurred in all groups. Results: The two-way ANOVA results showed that there was a significant difference between the karamunting leaf extract group, the group that was not given drug, and the group given calcium hydroxide with a value p<0.05. Conclusion: Based on the research conducted, it is concluded that the administration of karamunting leaf extract can reduce the number of macrophages in pulp inflammation. Keywords: calcium hydroxid, exposed pulp, karamunting leaf, macrophages, pulp inflammation.